THE CORRELATION BETWEEN SMOKING HABIT AND HYPERTENTION INCIDENT IN MEN IN THE COMMUNITY HEATH CENTER OF NGEMBAL KULON, KUDUS CITY - Rusnoto - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Smoking can interfere with the health, this fact cannot be denied, many diseases that have been proven become the result of smoking, directly or indirectly. The number of occurances of smoking in Indonesia was high, for man at 60%-70% in urban and 80%-90% in the rural. Based on WHO data in 2002, indonesia got the fifth hightest rank in consuming 215 billion cigarettes. The title of this research is “The Correlation between the Smoking Habit and Hypertension Incident in Men in the Community Health Center of Ngambal Kulon, Kudus City”. The purpose of this research was to describe the correlation between the smoking habit and hypertension incident in men in the community health center of Ngambal Kulon, Kudus City. The population was 159 people as the community who had hypertension and lived around the community heath center of Ngembal Kulon, Kudus city. The sample of this study was 32 people. This study belonged to the correlation descriptive and the cross-sectional approach. The result of this study was there is a correlation between the smoking habit and the hypertension incident in the community heath center Ngembal Kulon, Kudus city where most of the respondents had smoking habit and got hypertension. The total of respondents had smoking habit and hypertension is 26 respondents (81,3%)Keywords: smoking habit, hypertension, Ngembal